Hypoperfusion During Migraine and its Effect on the Retina (Texas Journal of Medical Science, 2023)
One of the most prevalent chronic, complex neurovascular illnesses, migraine, is primarily defined by recurring bouts of incapacitating headaches with aura appearances in up to one-third of patients. Nearly 15% of people get migraines, making it the third most common sickness in the world. Objective: This paper aims to study hypoperfusion during migraines and its Effect on the Retina